ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN REAL ESTATE AND PROPERTY DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
The study examines the effect of Current Ratio, Debt to Equity Ratio, Earning Per Share, Return On Investment, Size, and Growth of Sales on Stock Price. This research was conducted at the Real Estate and Property company listed in Indonesian Stock Exchange. The sampling method used purposive sampling. Relationship and (or) influence between variable is described by using multiple regression analysis. The results showed that Earning Per Share and Size has positive effect and significant to the Stock Price. Variable Current Ratio had positive effect but no significant to the Stock Price, whereas variable Debt to Equity Ratio, Return On Investment,andGrowth of Sales had negative effect and no significant to the Stock Price. Keywords: Stock Price, Current Ratio, Debt to Equity Ratio, Earning Per Share, Return On Investment, Size, and Growth of Sales